Echocardiographic predictors of cardiac erosion after amplatzer septal occluder placement. Issue 1 (30th September 2013) - Amin, Zahid
<x xml:space="preserve">Abstract</x> The risk of erosion after Amplatzer septal occluder (ASO) device placement in atrial septal defects is well described. Aortic rim deficiency and use of over‐sized device increase the risk of erosion. This study attempts to describe device characteristics, anatomical features and echocardiographic predictors that increase the risk of erosion. Methods: From 2005 through 2012, 12 new cases, with nine confirmed and three suspected device erosions where pre‐procedural, intra‐procedural, and/or post‐procedural echocardiograms were available and, were reviewed. Following parameters were evaluated: ASD location (high or low), rims deficiency and consistency, septal mal‐alignment, dynamic nature of the defect; device edge relationship toward the transverse sinus (TS), atrial free wall tenting and the size of the defect compared with the size of the device used for closure. Results: We found poor posterior rim consistency, aortic rim absence (in multiple views) and absent aortic rim at O degree in 100% of the patients. Septal mal‐alignment and dynamic ASD was present in nearly 50% of the cases. The device was over‐sized in three patients only. A 26‐mm device was the most common device that resulted in erosion. In cases, where patient had experienced bloody pericardial effusion and the device was in place, device tenting in the TS was observed. Surgical explantation of the device confirmed presence of erosion in all cases. Conclusion: Aortic rim absence in multiple views, poor posterior rim consistency, septal mal‐alignment, and dynamic ASD appear to be factors where erosion risk increases significantly. A thorough assessment of the device edge by echocardiography in short‐axis may show device tenting of the atrial free wall into the TS. This finding should be a strong indictor to recommend surgical removal of device after occurrence of pericardial effusion. © 2013 Wiley Periodicals, Inc.